Hierarchical voltage control strategy in interconnected power systems - Zainal Abidin, Mohd. Fhirdaus (2013)
In interconnected power systems, voltage variation is controlled in a centralized way which can only be done at the control centre to monitor and restore the voltage profile in the system within the permissible value. A large power system can have a complicated network which makes coordination a difficult task to come up with an efficient way to maintain system voltage profile. A decentralized area control will be developed based on the electrical distance concept with reference to the pilot bus using the sensitivity of the reactive power and voltage in the network. A voltage control scheme will be produced to maintain voltage profile in the decentralized control area by using a local element; which is the transformer by optimizing the tap setting to improve voltage profile in the system. This voltage control system will enable a better use of existing reactive power resources. A network of 118 bus system is used as a test case. The comparison with different implementation of the voltage control with generators only will be analyzed. A Matlab program will simulate the voltage profile by using Newton Raphson load flow. The impact of LTCs transformer appears by manipulating the admittance matrix and results on improving the system voltage profile to overcome bus voltage fluctuations.